Near-infrared Spectroscopy as a Potential Covid-19 Early Detection Method: A Review and Future Perspective - Muna E. Raypah; Asma Nadia Faris; Mawaddah Mohd Azlan; Nik Yusnoraini Yusof; Fariza Hanim Suhailin; Rafidah Hanim Shueb; Irneza Ismail; Fatin Hamimi Mustafa (MDPI, 2024)
Indexed by WOS/Scopus/ERA